2018
DOI: 10.1002/jctb.5874
|View full text |Cite
|
Sign up to set email alerts
|

Mesophilic microfiltration–anaerobic osmotic membrane bioreactor–membrane distillation hybrid system for phosphorus recovery

Abstract: BACKGROUND For the first time, a closed‐loop anaerobic osmotic membrane bioreactor–membrane distillation (AnOMBR‐MD) hybrid system integrated with periodic microfiltration (MF) extraction was investigated for simultaneous nutrient and energy recovery while maintaining high water quality for reuse. In addition, phosphorus (P) was recovered as a valuable material for agricultural purposes. RESULTS The AnOMBR‐MD system exhibited excellent nutrient (>99.9%) and organic removal (almost 100%) due to double‐layer fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Although promising, this configuration presents several challenges due to its high fouling propensity and lower reversibility, which were shown to result in a significant decrease of the water flux (Jw). Also, to tackle the salt accumulation due to reverse solute flux (RSF) and the consequent inhibition of the anaerobic biomass, the addition of microfiltration and the use of expensive salts as draw solutes were required previously [12,13,14]. As such, incorporating an FO membrane within the biological reactor appears challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Although promising, this configuration presents several challenges due to its high fouling propensity and lower reversibility, which were shown to result in a significant decrease of the water flux (Jw). Also, to tackle the salt accumulation due to reverse solute flux (RSF) and the consequent inhibition of the anaerobic biomass, the addition of microfiltration and the use of expensive salts as draw solutes were required previously [12,13,14]. As such, incorporating an FO membrane within the biological reactor appears challenging.…”
Section: Introductionmentioning
confidence: 99%
“…To get a better, stable, and long‐term CTA membrane operation, fouling of FO membrane should be controlled at the first two stages. Nevertheless, there might be irreversible fouling, which may need chemical cleaning, but the cost of chemicals may be applied, and chemical cleaning agents may bring destructive effect to FO membranes (Aftab et al., 2015; Chang et al., 2019; Goh et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…There have been some successful studies using MD to remove total phosphorus and nitrogen. 18,104 Kim et al 18 applied DCMD to treat livestock wastewater with high concentrations of suspended solids, total nitrogen and phosphorus. Their results showed that permeation flux can reach 38.8 L m −2 h −1 , and the rejection of total phosphorus and nitrogen can reach 99.4% and 90%, respectively.…”
Section: Mixed Matrix Membranementioning
confidence: 99%